Thread: How would you rearrange the following equation?

1. How would you rearrange the following equation?

0 = PR^n - Q(R^n)-1)/R-1

It needs to equal P. It's part of a modeling and problem solving question, I'm right with everything after the rearranging. Thank you.

2. Originally Posted by Liparulo
0 = PR^n - Q(R^n)-1)/R-1

It needs to equal P. It's part of a modeling and problem solving question, I'm right with everything after the rearranging. Thank you.
Do you mean: $0=\dfrac{PR^n-Q(R^n)-1}{R-1}$

or: $0=\dfrac{PR^n-QR^{n-1}}{R-1}$

or: $0=PR^n - \dfrac{QR^n-1}{R-1}$

or: $0=PR^n - \dfrac{QR^{n-1}}{R-1}$

3. Originally Posted by earboth

or: $0=PR^n - \dfrac{QR^n-1}{R-1}$
This one. Sorry, I know it's a basic question and I should be able to do it, but I'm just not clicking at the moment.

4. Originally Posted by Liparulo
This one. Sorry, I know it's a basic question and I should be able to do it, but I'm just not clicking at the moment.
1. Move the quotient to the other side of the equation:

$
PR^n = \dfrac{QR^n-1}{R-1}$

and then divide by $R^n$

$
P = \dfrac{QR^n-1}{R^n(R-1)}
$

5. Thank you very much. I knew it was simple algebra that was holding me back.